Microelectronics : an integrated approach - Howe, Roger T. (Prentice Hall electronics and VLSI series, 1997)
This book describes device physics and circuit design in the context of modern microelectronics integrated circuit technology. It introduces approaches to learning the core device physics and analog/digital circuit concepts that make the subject more accessible to the current generation of students. The authors have designed a concise, concentrated presentation, limiting coverage to only those concepts necessary for the understanding of devices and circuits.